Crucial role of craftsmanship spirit in fostering innovative behavior among skilled talents in the manufacturing sector - Li, Yuzhu; Zhang, Qiuyue; Yang, Wenyin (Frontiers in Psychology, 2025)
Innovation remains pivotal for establishing and sustaining a competitive edge within the manufacturing industry. Skilled talents play a vital role in driving innovation and entrepreneurship in this sector. Their creative prowess significantly determines the success of a nation's innovation-centric development strategy. Craftsmanship spirit emerges as an indispensable mental fortitude for exceptionally skilled talents. Drawing on social cognitive theory and social exchange theory, this study constructed a theoretical model to explore the intricate relationship between craftsmanship spirit and the innovative behavior of skilled talents, which was subsequently validated through empirical research.This study showed that craftsmanship spirit actively fostered the innovative behavior of skilled talents. This facilitation was mediated through two interconnected variables: innovative self-efficacy and knowledge sharing among skilled talents, with organizational innovation climate assuming a nuanced regulatory role. Consequently, enterprises are encouraged to nurture craftsmanship spirit, amplify innovative selfefficacy, promote knowledge sharing, and proactively instill an innovative climate within their organization. These measures can collectively inspire and amplify innovative behavior among skilled talents.